The Influence of the Board of Commissioners and the Board of Directors on Tax Avoidance with Gender Diversity as a Moderating Variable - Wahyuni Wahyuni; Analisa Analisa; Yusri Yusri; Sari Yanti (Transpublika Publisher, 2025)
This paper aimed to examine how the commissioners board and the board of directors impact tax avoidance, while also considering gender diversity as a moderating factor. This study analyzes all coal industry companies listed on the IDX (2020-2022) using purposeful sampling (48 data points). Multiple linear regression and Moderated Regression Analysis (MRA) were employed to examine variable relationships and moderating effects. The t-test results showed a noteworthy impact from both the board of commissioners and the board of directors on tax evasion. The significance value for the board of commissioners' impact was 0.014, which was below the threshold of 0.05. Similarly, the significance value for the board of directors' impact was 0.037, also below the threshold of 0.05. This suggests that both governing bodies had a noteworthy effect on tax avoidance. The F-test indicated that both the board of commissioners and the board of directors had a significant impact on tax avoidance as their significance values were less than 0.05. This suggests that both boards had a combined influence on tax avoidance. Additionally, the MRA test demonstrated that the inclusion of gender diversity in the board of commissioners led to a notable effect on tax avoidance, with a significance level lower than 0.05. Likewise, the presence of various genders in the board of directors had a notable impact on tax evasion, with a significance level lower than 0.05. These findings suggest that gender diversity may influence the dynamics between the board of commissioners, board of directors, and tax avoidance practices.